Ultrasonic measurements on thin samples: Experiment and numerical modeling - Yurikov, A.; Lebedev, Maxim; Pervukhina, M. (2016)
Ultrasonic velocity measurement method is a common practice for measuring elastic properties of rocks in laboratories. Standard cylindrical plugs of 40-100 mm length and 20-38 mm in diameter are usually used for such measurements. However, the maximal sizes of samples are sometimes restricted, especially when ultrasonic measurements are combined with desaturation/rehydration or dielectric analysis experiments. Such experiments are performed on relatively thin discs (~15 mm in length). However, the reliability of the results obtained on thin discs is unclear, as no direct comparison with results obtained on standard samples has been reported yet. Here we present results of laboratory ultrasonic measurements for a suite of thin and standard samples conducted under high confining pressure. Compressional and shear waves velocities obtained on thin and standard samples match each other within the experimental errors. We also present results of numerical simulations to support the outcome of the experimental work and to improve the understanding of wave propagation in the samples during laboratory ultrasonic measurements. The finite element method is used to simulate wave propagation along the experimental set-up caused by transmitted ultrasonic pulse. The results of the numerical modeling prove that transducers working in share mode also produce a compressional wave that propagates along the sample and can be recorded by a receiver. Simulated travel times of elastic waves are in a good agreement with experimentally obtained results.